2014
DOI: 10.4172/2329-6887.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives: Therapeutic Uses of Tobramycin

Abstract: Tobramycin has been around for over 40 years. This aminoglycoside antibiotic continues to be an invaluable part of our antibiotic armamentarium. It demonstrates concentration-dependent bactericidal activity, post antibiotic effect, and is minimally influenced by bacterial inoculum. Journal of PharmacovigilanceJou rn a l o f P harma c o v ig il a nc e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Doxycycilne merupakan bentuk turunan dari oksitetrasiklin dan memiliki waktuparuh lebih panjang dan ekskresi lebih lama. Doxycycilne baik digunakan untuk pengobatan penyakit karena riketsia, klamidia, mikoplasma dan spirocheta (Plumb, 2008) (Reyes et al, 2014).…”
Section: Pembahasanunclassified
“…Doxycycilne merupakan bentuk turunan dari oksitetrasiklin dan memiliki waktuparuh lebih panjang dan ekskresi lebih lama. Doxycycilne baik digunakan untuk pengobatan penyakit karena riketsia, klamidia, mikoplasma dan spirocheta (Plumb, 2008) (Reyes et al, 2014).…”
Section: Pembahasanunclassified
“…Research has proved that ginger could be used to cure certain ailments. Al-Achi (2007) reported that ginger is contraindicated in people Ewuziem, J.E., Onyenobi, V.O., Ironkwe, A.G. and Tokula, M.H [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] suffering from gallstones as the herb promotes the release of bile from the gall bladder. Also, Chen et al (2007) noted that ginger compounds are active against a form of diarrhea which is the leading cause of infant death in developing countries.…”
Section: Introductionmentioning
confidence: 99%